Can rotated words be processed automatically? Evidence from rotated repetition priming. - Benyhe, András; Csibri, Péter (Memory & Cognition, 2021)
Visual word processing has its own dedicated neural system that, due to the novelty of this activity, is unlikely to have acquired its specialization through natural selection. Understanding the properties of this system could shed light on its recruitment and the background of its disorders. Although recognition of simple visual objects is orientation invariant, this is not necessarily the case for written words. We used a masked repetition priming paradigm to find out whether words retain their readability when viewed in atypical orientations. Subjects had to read out upright target words that were preceded by rotated prime words of the same or different identity. Priming duration was varied in Experiment 1 to assess the temporal emergence of a rotated priming effect. In Experiment 2, the letter order of the prime words was reversed in order to differentiate the processing stage where priming occurs. The orientational pattern of the priming effects seen in our results mostly confirms earlier word recognition models, but also serves a more detailed view about the effects of orientation on word form processing.